Accurate and efficient numerical solutions for the Saint Venant equations of open channel flow - Crossley, Amanda Jane (1999)
Within the eld of hydraulics there is a growing trend towards the use of computer based models, which have proven to be an invaluable tool in engineering. A range of commercial packages is available which encompass different mathematical models and a variety of solution strategies.